Spiritual Leadership’s Impact on Project Success: Project Goal Clarity and Perceived Organizational Support as Mediating and Moderating Factors - Cheng-Wen Lee; Adil Zareef Khan (International Journal of Business and Economic Affairs, 2024)
This study aims to investigate the impact of spiritual leadership on project outcomes and to explore the possible mediating effect of project goal clarity, as well as the moderating role of perceived organizational support. Grounded in social exchange theory, this study contributes to the literature by investigating the mechanisms—specifically project goal clarity—that connect spiritual leadership with project success and by examining the role of employees’ perceptions within the organization, such as perceived organizational support. The quantitative analysis involved data from 258 employees in the IT sector, specifically from private software firms. Data analysis was performed using the Preacher and Hayes process method with SPSS version 21.0 and Amos. The results indicate that spiritual leadership has a positive effect on project success. Furthermore, the study shows that project goal clarity partially mediates the relationship between spiritual leadership and project success, while perceived organizational support moderates the association between project goal clarity and project success.